Footloose capital, market access, and the geography of regional state aid - Gianmarco I. P. Ottaviano (Hamburg Institute of International Economics (HWWA), 2001)
The global welfare implications of home market effects in trade models with imperfect competition are little understood. This paper proposes a simple model in which such implications can be easily analyzed. It shows an overall tendency of imperfectly competitive sectors to inefficiently cluster in locations that offer market access advantages. The more so the stronger the market power of firms as well as the intensity of increasing returns to scale and the lower the trade costs. As such features are likely to differ widely across sectors, those results provide theoretical ground to the promotion of regional policies that are also sectorspecific and not only region-specific as currently in the EU.
Keywords: F12; R13; L13; 330; economic integration; specialization; home market effect; regional disparities; regional policy; Wirtschaftsunion; Neue Außenhandelstheorie; Direktinvestition; Standorttheorie; Regionale Konzentration; Neue ökonomische Geographie; Industriestruktur; Regionale Disparität; EU-Regionalpolitik; Landesgröße; EU-Staaten; home market effect